2022
DOI: 10.3389/fmicb.2022.932467
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the antimicrobial activity of antiseptics against clinical Acinetobacter baumannii strains isolated from combat wounds

Abstract: Healthcare-associated infections (HCAIs) are among the most prominent medical problems worldwide. In the context of increasing antibiotic resistance globally, the use of antiseptics as the main active agent and potentiator of antibiotics for the treatment of purulent-inflammatory complications of traumatic wounds, burns, and surgical wounds can be considered to tackle opportunistic infections and their prevention during war. This study presents a comparative investigation of the antimicrobial efficacy of antis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…This article is a continuation of a study, part of which was published earlier [11], and was devoted to the antimicrobial properties of antiseptics against MDR clinical strains of Gram-negative bacteria, isolated from combat wounds. Our study is a fragment of scientific project «Research of the biological properties of pathogens of HCAIs and the development of means of combating them».…”
Section: Materials and Methods Of The Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…This article is a continuation of a study, part of which was published earlier [11], and was devoted to the antimicrobial properties of antiseptics against MDR clinical strains of Gram-negative bacteria, isolated from combat wounds. Our study is a fragment of scientific project «Research of the biological properties of pathogens of HCAIs and the development of means of combating them».…”
Section: Materials and Methods Of The Researchmentioning
confidence: 99%
“…MBC was taken as the lowest concentration of the antiseptic, at which colony growth does not occur under the given conditions. Three replicates were performed for each isolate of E. coli and antimicrobial component [11].…”
Section: Mic (Minimum Inhibitory Concentration) and Mbc (Minimum Bact...mentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies have demonstrated efficacy of PHMB on a Gram-negative bacteria and Gram-positive bacteria, [43][44][45][46][47] fungi, [48][49][50] certain viruses, 51,52 and single-celled parasites (amoeba). 53,54 PHMB has also been shown to show antibiofilm activity on biofilms, 31,47,48,[55][56][57][58] including wound biofilms.…”
Section: Experimental Assessment Of Anti-biofilm Activitymentioning
confidence: 99%